2019
DOI: 10.1111/tops.12414
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Structured Vocalizations in Songbirds and Humans: A Comparative Analysis

Abstract: Humans and songbirds face a common challenge: acquiring the complex vocal repertoire of their social group. Although humans are thought to be unique in their ability to convey symbolic meaning through speech, speech and birdsong are comparable in their acoustic complexity and the mastery with which the vocalizations of adults are acquired by young individuals. In this review, we focus on recent advances in the study of vocal development in humans and songbirds that shed new light on the emergence of distinct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 64 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…Although some studies found evidence for a language ability-aggression relation at around 18 months (Dionne et al, 2003;Girard et al, 2014), research into this association during infancy and early toddlerhood is limited. Reason for this might be that the assessment of language development this early (i.e., during infancy), which focuses on babbling, vocalizing, and comprehension and production of first words (Lipkind et al, 2019), is very complex in itself, thereby leaving a much smaller number of studies that link these abilities to behavior problems.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies found evidence for a language ability-aggression relation at around 18 months (Dionne et al, 2003;Girard et al, 2014), research into this association during infancy and early toddlerhood is limited. Reason for this might be that the assessment of language development this early (i.e., during infancy), which focuses on babbling, vocalizing, and comprehension and production of first words (Lipkind et al, 2019), is very complex in itself, thereby leaving a much smaller number of studies that link these abilities to behavior problems.…”
Section: Introductionmentioning
confidence: 99%
“…The way in which these vocal units emerge shows remarkable similarities between infants and zebra finches (a much used model species for examining vocal learning), and these observations indicate an important role for motor variability in both species. In contrast to what is commonly assumed, Lipkind et al () suggest that songbird subsong and its development into a more structured song is more comparable to the phonation stage in infants than to human babbling. Observational and experimental data on the development of vocal unit combinations show more parallels between the species, like the transitioning from a repetitive to a diverse production of units.…”
Section: Insights From Comparative Agl Studiesmentioning
confidence: 79%
“…The above‐mentioned studies focus on the abilities for detecting and discriminating structural patterns using some kind of perceptual discrimination task. A different comparative approach is taken by Lipkind et al (). They focus on development of sequences in sound production in human infants and songbirds.…”
Section: Insights From Comparative Agl Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this view, it has been found that learning the motifs and syntax involves independent mechanisms (Lipkind et al 2017). The computational study of hierarchical structures and compositional behaviour can also lead to insights into the development of human locomotion and language as there are striking conceptual parallels (Dominici et al 2011;Lipkind et al 2013;Ding et al 2015;Lipkind et al 2019).…”
Section: Introductionmentioning
confidence: 94%